THE CHARACTERIZATION OF THE Ca-K GEOPOLYMER/SOLIDIFIED FLUID FLY-ASH INTERLAYER - Ivana Perna; Monika Supova; Hanzlicek Tomas (Ceramics-Silikáty, 2016)

(untitled)
A Ca-K geopolymer matrix based on clay material and blast-furnace slag was filled with aggregates, ash pellets made from fluid fly ash, and the interlayer formed between the two components was studied. The scanning electron-microscopy investigation of the inseparable interlayer demonstrated that the pellets were not only enveloped in a geopolymer matrix but also incorporated through a thin, yet identifiable, surface pellet layer. The migration of calcium and potassium ions was detected and that changes in the quantity of these ions arise from their mobility. The interlayer on the edges of ash pellets was also studied by infrared analysis, which in this layer proved bands belonging to both participants, the matrix and the pellets. Based on the results, two different materials prepared from wastes could be used for the preparation of a new composite material and thus facilitate waste-material disposal.